27. QUALITY OF MEDICAL RECORDS AT DEPARTMENT OF GENERAL SURGERY IN YEN LAC DISTRICT HEALTH CENTER IN 2022 (Vietnam Journal of Community Medicine, 2023)
Introduction: Medical records constitute a legal and professional document regarding the activities of medical staff in hospitals. Objective: This study was conducted with the aim of assessing the quality of medical records at the Department of General Surgery in Yen Lac District Health Center in 2022. Methods: This study applied a cross-sectional research design with a a sample size of 400 medical records at the Department of General Surgery in Yen Lac District Health Center in 2022. Findings: 53.8% of records achieved good quality, whereas the quality writing of part C (clinical findings and testing results), part B (patient medication treatment) and part A – General information has the lowest rate of good quality of writing with about 55%. Part D – Summary had the achieved rate as highest as 73.8%. Conclusions: We recommended increasing training on writing medical records for health providers, improving the monitoring and evaluation (medical record review and inspection of the leaders), and issuing appropriate incentive and reward mechanisms. At the same time, Yen Lac District Health Center should focus on revising the medical record template.
Keywords: Medical record, completeness, timeliness, Yen Lac District Health Center.